2020
DOI: 10.3310/hta24390
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care creatinine tests to assess kidney function for outpatients requiring contrast-enhanced CT imaging: systematic reviews and economic evaluation

Abstract: Background Patients with low estimated glomerular filtration rates may be at higher risk of post-contrast acute kidney injury following contrast-enhanced computed tomography imaging. Point-of-care devices allow rapid measurement of estimated glomerular filtration rates for patients referred without a recent estimated glomerular filtration rate result. Objectives To assess the clinical effectiveness and cost-effectiveness of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 105 publications
(222 reference statements)
0
13
0
1
Order By: Relevance
“…29 A recent review suggests that the use of point-ofcare testing may reduce costs to the health care system by reducing unnecessary delays in CT scanning appointments. 30 However, sufficient validation is needed before clinical implementation since the accuracy appears to differ between different point-of-care devices. 30 The CM dose should be minimized in order to reduce neurotoxic effects but must be sufficient to enhance attenuation differences between normal and pathological tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 A recent review suggests that the use of point-ofcare testing may reduce costs to the health care system by reducing unnecessary delays in CT scanning appointments. 30 However, sufficient validation is needed before clinical implementation since the accuracy appears to differ between different point-of-care devices. 30 The CM dose should be minimized in order to reduce neurotoxic effects but must be sufficient to enhance attenuation differences between normal and pathological tissues.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, sufficient validation is needed before clinical implementation since the accuracy appears to differ between different point-of-care devices. 30 The CM dose should be minimized in order to reduce neurotoxic effects but must be sufficient to enhance attenuation differences between normal and pathological tissues. It has been reported that the incidence of PC-AKI proportionally correlates with the injected the CM dose especially among high-risk populations with preexisting renal insufficiency or diabetic neuropathy, 31 thereby emphasizing the need for individual adjustment of CM dose.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews by Silver et al 29 and Corbett et al 30 highlight the applicability of models for predicting CIN risk. Although the first of these studies only investigated cases involving coronary angiographic procedures (rather than contrast-enhanced CT), it stated that the best performing risk prediction models of the 12 analyzed included assessment of chronic kidney disease, age, diabetes mellitus, heart failure, and hypotension or shock.…”
Section: Methodsmentioning
confidence: 99%
“…Revisões sistemáticas como as de Silver et al 29 e Corbett et al 30 citam a aplicabilidade de modelos preditivos de risco para NIC. O primeiro estudo, apesar de abordar apenas casos envolvendo procedimentos coronarianos (e não TC contrastada), cita que, ao analisar 12 diferentes modelos de predição de risco, os melhores destacavam-se por incluírem avaliações sobre doença renal crônica, idade, diabetes melito, insuficiência cardíaca e hipotensão ou choque; já o segundo cita o custo-benefício favorável da implementação de um sistema de diagnóstico de três fases para classificar o paciente que necessitaria de medidas profiláticas para NIC.…”
Section: Materiais E Métodosunclassified
“…Access to SCr testing remains a critical barrier in many African health care settings [ 25 ], and increased availability of point-of-care devices to measure SCr across all levels of health care could substantially improve the recognition and management of AKI in resource-limited settings. The majority of studies assessing performance of point-of-care devices to measure SCr have been conducted in high-income settings in adult populations [ 26 28 ] where SCr levels are substantially higher than pediatric populations. Therefore, there is a need to evaluate point-of-care tests in pediatric populations where small changes in SCr may constitute AKI.…”
Section: Introductionmentioning
confidence: 99%